Language Acquisition of Deaf Children at SLB Bhina Putera, Surakarta: A Psycholinguistic Analysis - Dyah Ayu Pitaloka; Ani Rakhmawati (Universitas Nusantara PGRI Kediri, 2026)
Language acquisition in children with hearing impairment is affected by limited auditory input, which influences their spoken language development. Consequently, deaf children rely more on visual cues, gestures, and situational context in communication. This study aims to describe Indonesian language acquisition in deaf children at SLB Bhina Putera Surakarta by examining four linguistic aspects: phonology, morphology, semantics, and syntax, as well as identifying learning strategies that support communication. This research employed a descriptive qualitative method. Data were collected through in-depth interviews with teachers and supported by relevant literature. Data analysis was conducted by classifying findings based on linguistic aspects and interpreting them descriptively. The results show that language acquisition in deaf children is functional and context-dependent. Phonologically, difficulties in producing certain sounds were observed. Morphologically, children mainly used basic word forms with limited variation. Semantically, meaning comprehension relied on visual experience and context. Syntactically, sentence structures often showed word order reversals and did not fully conform to standard Indonesian grammar, yet remained communicative. Visual-based learning strategies that consider individual characteristics were found to support language development in deaf children.